The Influence Of Work Discipline And Financial Compensation On Performance Of Employees In National Private Shipping And Logistics Industry - Prety Diawati; Eva Yuniarti Utami; Mulyadi; Rendi Randika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Human resources and personnel management are crucial for businesses in managing, coordinating, and employing staff so that they can work efficiently to meet organizational goals. A company's human resources must be competently managed to strike a balance between employee needs and the requirements and capabilities of the organization. The key to the business's productive and equitable growth is this equilibrium. The productivity of a company's personnel has a significant impact on the growth of its operations and organizational structure. In this study, the impact of direct cash pays and the use of workplace rules on employee performance is examined. 100 individuals from each employee division's population made up the sample. The impact of direct financial support and the imposition of work discipline on employee performance levels is examined using the multiple regression method. The study's findings demonstrate that among the four independent variables salary, wages, incentives, and work discipline only incentive, with a t-value less than the t-table, has no bearing on the independent variable performance.